Ministry of social solidarity decree no 9 of the year 2014 amending the decree of the minister of finance no 554 of the year 2007 on the rules implementing the social insurance Law = قرار وزاري رقم 9 لسنة 2014 بشأن تعديل قرار وزير المالية رقم 554 لسنة 2007 بالقواعد المنفذة لقانون التأمين الاجتماعي الصادر بالقانون رقم 79 لسنة 1975 - Egypt; The middle east library for economic services, translator. (2025)
Ministry of Social Solidarity decree no. 9 of the year 2014 amending the decree of the minister of finance no. 554 of the year 2007 on the rules implementing the social insurance law promulgated by law no. 79 of the year 1975 وزارة التضامن الاجتماعى قرار رقم 9 لسنة 2014 بشأن تعديل قرار وزير المالية رقم 554 لسنة 2007 بالقواعد المنفذة لقانون التأمين الاجتماعى الصادر بالقانون رقم 79 لسنة 1975